Models of Individual Behavior and Implications for Environmental Policy - Jeroen C.J.M. van den Bergh; Ada Ferrer-I-Carbonell; Guiseppe Munda (Tinbergen Institute, 1998)
Most insights of environmental economics are in line with the standard neoclassicaleconomic model of rational behaviour, formulated in terms of maximization of utility ingeneral, or profits in particular. The standard theory of environmental policy is a casein point. However, the maximization hypothesis and its methodological foundation havebeen criticized on many grounds, related to a lack of either logical or empirical content.Moreover, over the years a great many alternative models of behaviour have been proposed.Both criticism and alternatives are surveyed here. In the context of environmentaleconomics behavioural assumptions have been most significant for the development ofeconomic valuation theory and environmental policy theory. The focus here will be onenvironmental policy theory.
Keywords: 330; Umweltökonomik; Verhaltensökonomik; Umweltpolitik; Theorie